"I'm Running So You Can Be Happy and I Can Keep My Scholarship" - Joseph N. Cooper; Jewell E. Cooper (University of Kansas Libraries, 2015)
The purpose of this study was to examine the experiences of two groups of Black male college athletes at a Division I historically White institution (HWI) to better understand the key contributors that influenced their academic performance levels, academic engagement, and the quality of their overall college experiences. Two focus groups were conducted with 10 Black male college athletes enrolled at a Division I HWI and a demographic questionnaire was administered to ascertain a better understanding of their personal backgrounds, college academic experiences, and college athletic experiences. Role theory was incorporated as a theoretical lens to investigate the participants' identity salience, role commitments, and overall college experiences. Findings revealed participants from each group shared common experiences encountering role conflict. However, the coping strategies and academic performance outcomes varied between each group. Implications for policy and practice are discussed.